Dampak Misa Jumat Pertama Bulan terhadap Spiritualitas Calon Guru Pendidikan Agama Katolik - Bavo, Servasius; Meliyanto, Adi Ria Singir; Satya Bhakti, Angga (Vocat : Jurnal Pendidikan Katolik, 2025)
This study aims to explore students' understanding of the First Friday Mass at Sekolah Tinggi Agama Katolik (STAKat) Negeri Pontianak, its impact on their spirituality as future Catholic Religious Education teachers, and the obstacles they face in participating in the mass. The research was conducted from July 30 to September 9, 2024, at STAKat Negeri Pontianak. Informants in this study consisted of three main groups: students from the 2022, a lecturer, and the Vice Chairman III. The findings showed that students at STAKat Negeri Pontianak had a solid understanding of the First Friday Mass as a form of devotion to the Sacred Heart of Jesus and an essential part of the Catholic faith. This mass has a positive impact on students' spirituality, especially in shaping attitudes of faithfulness to God's word, compassion for others, forgiveness, humility, and a willingness to sacrifice qualities vital for future Catholic Religious Education teachers. However, participation in the mass was hindered by several challenges, such as health issues, conflicting academic or work schedules, and a lack of motivation that causes some students to perceive the mass as less important. Nevertheless, the First Friday Mass continued to play a significant role in supporting students’ spiritual development.